Kants teleologische Überlegungen zur Menschenwürde in der Vorlesung über Naturrecht Feyerabend - Moledo, Fernando (Studia Kantiana, 2023)
In this paper I deal with an argument for the foundation of human dignity that Kant sketches in the introduction to his lecture Feyerabend on natural law (1784). After presenting very briefly Kant’s discussion of Achenwall’s concept of value I argue that the starting point of the argument on human dignity that Kant develops in the introduction to the lecture is teleological. I discuss then the problems that such a starting point inevitably entails regarding Kant´s practical philosophy and offer an explanation as to why Kant was able to include this argument in the introduction to his lecture despite the problems it raises. Finally I claim that despite these problems the central idea of the argument reflects a fundamental idea of Kant’s thought on human dignity. In support of the latter I refer to the fact that Kant turns to the same central idea of the argument some years later in his discussion of teleology developed in the Critique of Judgment (1790).